On the taxonomy of the Brazilian flea beetle genus Miritius Bechyné & Bechyné (Coleoptera: Chrysomelidae: Galerucinae: Alticini: Monoplatina) with description of two new species - Morais, Ana Carla C.; Ribeiro-Costa, Cibele S.; Linzmeier, Adelita M. (Zootaxa, 2016)
A taxonomic study was performed on the Brazilian genus Miritius Bechyné & Bechyné of Monoplatina, Alticini. Here Miritius and two of its species are redescribed and descriptions for another two new species were provided: Miritius abdominalis Morais & Linzmeier sp. nov. (Mato Grosso, Brazil) and Miritius claudius Morais & Linzmeier sp. nov. (Mato Grosso and Mato Grosso do Sul, Brazil). For the first time characters of the male and female genitalia, illustrations and a key to the Miritius species are presented.